WALLABY Pilot Survey: Star Formation Enhancement and Suppression in Gas-rich Galaxy Pairs - Qifeng Huang; Jing Wang; Xuchen Lin; Se-Heon Oh; Xinkai Chen; B. Catinella; N. Deg; H. Dénes; B. -Q. For; B. S. Koribalski; K. Lee-Waddell; J. Rhee; et al. (The Astrophysical Journal)
Galaxy interactions can significantly affect the star formation in galaxies, but it remains a challenge to achieve a consensus on the star formation rate (SFR) enhancement in galaxy pairs. Here, we investigate the SFR enhancement of gas-rich galaxy pairs detected by the Widefield ASKAP L -band Legacy All-sky Blind surveY. We construct a sample of 278 paired galaxies spanning a stellar mass ( M _* ) range from 10 ^7.6 to 10 ^11.2 M _⊙ . We obtain individual masses of atomic hydrogen (H i ) for these paired galaxies using a novel deblending algorithm for H i data cubes. Quantifying the interaction stages and strengths with parameters motivated by first-principles analysis, we find that, at fixed stellar and H i mass, the alteration in the SFR of galaxy pairs starts when their dark matter halos are encountered. For galaxies with a stellar mass lower than 10 ^9 M _⊙ , their SFRs show tentative suppression of 1.4 σ after the halo encounter, and then become enhanced when their H i disks overlap, regardless of mass ratios. In contrast, the SFRs of galaxies with M _* > 10 ^9 M _⊙ increase monotonically toward smaller projected distances and radial velocity offsets. When a close companion is present, a pronounced SFR enhancement is found for the most H i -poor high-mass galaxies in our sample. Collecting the observational evidence, we provide a coherent picture of the evolution of galaxy pairs and discuss how the tidal effects and hydrodynamic processes shape the SFR enhancement. Our results provide a coherent picture of gas-rich galaxy interactions and impose constraints on the underlying physical processes.